Pertanggung jawaban Notaris dalam Pembuatan Akta Pernyataan Nominee Pemegang Saham oleh Warga Negara Asing dalam Pendirian Perseroan Terbatas - Sudiana, Nana; Sinaulan, Ramlani Lina; Koto, Zulkarnain (Postgraduate of Jayabaya University, 2023)
Discussion on the responsibility of a notary for making a deed of statement of a shareholder Nominee by a foreign national in the establishment of a limited liability company. Research conducted using normative juridical methods. In Nominee agreements/statements between foreigners and Indonesian citizens it is closely related to the notary as the authorized official in making the Nominee agreement/statement deed, which as stated in UUJN that every deed made by the interests of the parties appear before the notary, then the deed has the power as authentic deed, but in reality the purpose of making this Nominee agreement/statement is to safeguard the assets that are the object of the Nominee even though this practice is often motivated by bad intentions, one of which is to avoid laws and regulations that limit the ownership of foreign citizens or more furthermore as a form of money laundering practices.